Effects of Butea superba on reproductive systems of rats - Aranya Manosroi (2018)
The effects of Butea superba on the reproductive system in male Wistar rats were investigated. The animals were fed daily with the powdered crude drug suspended in distilled water by a gastric tube at the dose of 2, 25, 250 and 1250 mg/kg body weight for 8 weeks. Rats fed with 1 ml of distilled water were used as a negative control. The weights of all vital organs in all treated groups were not different from the control. The percentage weight ratios of body weights of seminal vesicles and prostate glands were not different from the control, except that the testis of the group fed with 1250 mg/kg was significantly different from the control and the other treated groups. In addition, the sperm counts in this group showed about 16% more than the control group. Hematology as well as the liver and kidney function of all treated groups showed no difference from the control. B. superba, drug at 250 mg/kg which was 100 times more than the Thai FDA recommended dose for humans appeared to be safe in rats. The crude drug has demonstrated an increase tendency on testis weight and sperm counts in rat. The information from the present study can be used to explain the Thai folklore application of this plant in Thailand. © 2006 Elsevier B.V. All rights reserved.